Cocoa pod borer Conopomorpha cramerella snellen infestation under shade and control treatments - Bakar, Saripah (2012)
Cocoa pod borer (CPB) is the most serious pest of cocoa and the infestation caused severe losses of cocoa crop hence production in Malaysia although several control approaches had been implemented. Management tactics including thinning of shade trees in mature cocoa plantation gained less attention by cocoa growers. Chapters 3, 4 and 5 reported in this thesis were examining effects of different levels of available shade trees, which are Light, Medium and Heavy Shade. These studies were conducted in inter-block and within block, and parameters studied were CPB eggs distribution and infestations. The results showed that different levels of shade affected the distribution of CPB eggs, hence influenced the severity of infestation. Findings show that an aggregated distribution, mean, entry and exit holes, CPB infestation during low and peak crop seasons and Average Damage Severity Index (ADSI) values were found to be highest at the Heavy Shade Block and significantly different with Medium and Light Shade Blocks. The results will useful to envisage the seriousness of CPB infestation (Chapter 4). It was denoted that heavy shade will lead to more serious infestation compared with medium and light shade. However, there was no significant different of different shade levels in small size plantation (Chapter 5) compared with bigger plantation (Chapters 3 and 4). This might influence by flying capability of CPB which can fly within short distance, thus was capable to oviposit their eggs at adjacent trees regardless to the different shade level. Based on the egg distribution and infestation level, the selection of appropriate control approaches will be carried out to reduce the yield loss caused by the CPB. It is postulated that thinning of the heavy existing shade trees to light shade level will help in reducing the population built-up of CPB, therefore reducing its infestation. Aside of management approaches by thinning of shade trees, CPB infestation may be reduce by using other techniques. Two different spraying calendars of insecticide and biological control agent were studied (Chapters 6 and 7). The results indicated that Cocoa Black Ants (CBA) were capable in reducing CPB infestation more than insecticide applications especially during low crop season. Number of entry and exit holes, damage category and ADSI values can be good indicators in evaluating the effectiveness of each control; however sampling of CPB eggs was more important in determining the yield later on. Overall, major findings from these studies especially necessity to thinning heavy shade trees and potential use of CBA as biological control agent must be disseminated to cocoa smallholders, due to both techniques may succeed in reducing the infestation caused by the CPB.